Globalisation and its Impact on Agriculture: an Overview of Kohima District, Nagaland, India - Yano, Keneikhoto; Lanusosang, T. (International Journal of Bio-resource and Stress Management, 2023)
Agriculture is the basis and key to socio-economic development of any society in the world. Each society, particularly of the tribal one has its well defined traditional agricultural practices. But the knowledge inherited by the tribal people for its management which is the product of over centuries of experience, skill and information being threatened at this age of globalisation. Kohima district of Nagaland state is the capital cosmopolitan city with a mixture of all the tribes of Nagaland including those from mainland India, however, Angami and Rengma Nagas are the dominants. It revealed that the traditional knowledge is deteriorating at an alarming rate due to the impact of globalisation. No doubt the one sided new technology and machinery tools have made the work much easier and faster but it has neglected the other sensitive side of the world which is the environment. The present study is thus an attempt to overview the vast indigenous knowledge, rich culture and traditions practised for the agricultural management and the reasons responsible for the loosening of the grip of agricultural sustainability in the region.